Promoting Motivation in Writing ELT Through Infographic - Sutrisno Sadji Evenddy; Ezis Japar Sidik; Dhafid Wahyu Utomo (Journal of Linguistics, Literacy, and Pedagogy, 2023)
This article examines the potential of infographics as a tool for promoting motivation in English language teaching (ELT), specifically focusing on the development of writing skills. Motivation is crucial in language learning, and educators are constantly seeking innovative approaches to engage students and foster a passion for writing. Infographics, with their visually appealing and information-rich nature, offer a promising avenue for achieving this goal. By incorporating infographics into writing instruction, educators can tap into their visual appeal and interactive elements to stimulate students' curiosity and enhance comprehension. Infographics also empower students by providing a sense of ownership and autonomy over their writing, allowing them to showcase their achievements in a visually compelling manner. However, implementing infographic-based strategies in writing ELT requires addressing challenges such as cultural relevance and accommodating diverse learner needs. Despite these challenges, infographics have the potential to revolutionize writing instruction by creating an engaging and inclusive learning environment that promotes motivation and improves writing proficiency.